SLC28 and SLC29 families of nucleoside transporters in GtoPdb v.2025.3 (IUPHAR/BPS Guide to Pharmacology CITE, 2025)
Nucleoside transporters are divided into two families, the sodium-dependent, concentrative solute carrier family 28 (SLC28) and the equilibrative, solute carrier family 29 (SLC29). The endogenous substrates are typically nucleosides, although some family members can also transport nucleobases and organic cations [1].